The Effect of Islamic Corporate Social Responsibility and Sharia Governance on the Financial Performance of Islamic Financial Institutions - Hastina, Hastina; Wijayanti, Rahma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to examine the influence between Islamic Corporate Social Responsibility (ICSR) and Sharia Governance on the financial performance of Islamic Financial Institutions listed on the ISSI (Indonesian Sharia Stock Index) during the period 2013-2022. The method used in this research is a quantitative approach using Panel Data Regression analysis with the help of Stata 18 software. The data used comes from the annual report of each company. The population is all Islamic Financial Institutions listed on the ISSI. Sampling is done using the Purposive Sampling technique with the number of samples obtained from as many as 5 Islamic Financial Institutions with a total of 35 observation data. The results showed that ICSR and Sharia Governance influence the company's financial performance as measured using Return on Equity (ROE). Thus, this research concludes that ICSR positively affected the IFI’s financial performance. Then the measurement of Sharia Governance using the number of Sharia Supervisory Board meetings can be used to determine the condition of the Company's financial performance.